Lignocellulosic biomass: Acid and alkaline pretreatments and their effects on biomass recalcitrance – Conventional processing and recent advances - Lorenci Woiciechowski, Adenise; Dalmas Neto, Carlos José; Porto de Souza Vandenberghe, Luciana; de Carvalho Neto, Dão Pedro; Novak Sydney, Alessandra Cristine; Letti, Luiz Alberto Junior; Karp, Susan Grace; Zevallos Torres, Luis Alberto; Soccol, Carlos Ricardo (Bioresource technology, 2020)
•Pretreatments to overcome recalcitrance and valorise biomass fractions are reviewed.•Mild and classical industrial thermochemical treatments are compared.•New patents of innovative acid and alkaline or combined treatments are presented.•China, USA and South Korea are the major patent applicants in this field.•Mild acid pretreatment is identified as the most promising technology. Lignocellulosic biomass is one of the most abundant organic resources worldwide and is a promising source of renewable energy and bioproducts. It basically consists of three fractions, cellulose, hemicelluloses and lignin, which confer a recalcitrant structure. As such, pretreatment steps are required to make each fraction available for further use, with acidic, alkaline and combined acidic-alkaline treatments being the most common techniques. This review focuses on recent strategies for lignocellulosic biomass pretreatment, with a critical discussion and comparison of their efficiency based on the composition of the materials. Mild pretreatments usually allow the recovery of the three biomass fractions for further transformation and valorisation. An insight is provided of newly developed technologies from recently filed patents on lignocellulosic biomass pretreatment and the transformation of agro-industrial residues into high value-added products, such as biofuels and organic acids.